Strategi Kepala Sekolah, Kompetensi Pedagogik Dan Profesional, Guru Pendidikan Agama Islam - Tasliyah, Avif Puti; Bunyamin, Andi; Hasibuddin (Journal of Gurutta Education, 2023)
In the education unit, the principal plays an important role in advancing the school he leads. In general, school principals are obliged to manage and empower their resources to achieve educational goals in the concerned educational unit, broadly speaking, through planning, organizing, implementing, and controlling. This study aims to determine the strategies used by school principals in developing teacher competencies in an effort to develop teacher pedagogic and professional competencies at SMPIT Darussalam Makassar. This study uses a qualitative research approach. Data was collected through the methods of observation, interviews, and documentation. The data obtained in the field is then compiled by selecting and simplifying the data. Furthermore, data presentation is carried out so that conclusions can be drawn. The results showed that the strategies used by the principal in developing the pedagogic and professional competence of teachers at SMPIT Darussalam Makassar include: controlling learning activities in the classroom; carrying out clinical supervision of PAI teachers four times in two (two) semesters; The obstacles faced by school principals in efforts to develop pedagogic competence and professional competence are the time involved in carrying out regular clinical supervision and the existence of solid work responsibilities and other activities related to learning